Female reproductive dormancy in Drosophila is regulated by DH31-producing neurons projecting into the corpus allatum - Kurogi, Yoshitomo; Imura, Eisuke; Mizuno, Yosuke; Hoshino, Ryo; Nouzova, Marcela; Matsuyama, Shigeru; Mizoguchi, Akira; Kondo, Shu; Tanimoto, Hiromu; Noriega, Fernando G; Niwa, Ryusuke (Development (Cambridge, England), 2023)
Female insects can enter reproductive diapause, a state of suspended egg development, to conserve energy under adverse environments. In many insects, including the fruit fly, Drosophila melanogaster, reproductive diapause, also frequently called reproductive dormancy, is induced under low-temperature and short-day conditions by the downregulation of juvenile hormone (JH) biosynthesis in the corpus allatum (CA). In this study, we demonstrate that neuropeptide Diuretic hormone 31 (DH31) produced by brain neurons that project into the CA plays an essential role in regulating reproductive dormancy by suppressing JH biosynthesis in adult D. melanogaster. The CA expresses the gene encoding the DH31 receptor, which is required for DH31-triggered elevation of intracellular cAMP in the CA. Knocking down Dh31 in these CA-projecting neurons or DH31 receptor in the CA suppresses the decrease of JH titer, normally observed under dormancy-inducing conditions, leading to abnormal yolk accumulation in the ovaries. Our findings provide the first molecular genetic evidence demonstrating that CA-projecting peptidergic neurons play an essential role in regulating reproductive dormancy by suppressing JH biosynthesis.
Keywords: Drosophila melanogaster; Reproduction; rozmnožování; Corpus allatum; Reproductive dormancy; Drosophila Proteins; Female; zvířata; neurony; Diuretic hormone 31; Corpora Allata; corpora allata; proteiny Drosophily; ženské pohlaví; hmyzí hormony; Diapause; Juvenile Hormones; Insect Hormones; Neurons; Juvenile hormone; Drosophila; juvenilní hormony; Animals